PREDIKSI POTENSI KEBANGKRUTAN DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE MODIFIKASI - Reisa Nurul Fadilah (Jurnal Ilmu Akuntansi, 2022)
This study aims to determine the potential for bankruptcy of the company by using a prediction tool, namely Altman Z-Score Modification. The sample used in this study is 7 companies with 24 population financial statements in the property and real estate subsector listed on the Indonesian stock exchange with an observation period in 2018-2021. The method used is a qualitative descriptive analysis technique. The data is processed from secondary data in the form of financial statements that are officially accessed through the Indonesian stock exchange database. The non-probability method used is the purvosive sampling method and the data is processed using the modified Altman Z-Score formula. The results showed that in the gray zone with a score of 1.1-2.6, namely PT Agung Podomoro Land Tbk in, PT Alam Sutera Realty Tbk in 2018-2021 and PT PP Property Tbk in 2020-2021 and in a safe zone condition. with a score of > 2.6, namely PT Jaya Real Property Tbk, PT Nusantara Almazia Tbk, Plaza Indonesia Realty Tbk, PT Pakuwon Jati Tbk in 2018-2021.